The Controversy of Muhammad Baqir Ash-Sadr's Thoughts (Eastern Capitalist) with the Thoughts of Karl Marx and Max Weber (Western Capitalists) in the Context of Global Islamic Economic System - Ahmed Fernanda Desky (International Journal Ihya' 'Ulum al-Din, 2022)
The fight in the globalization field between Eastern business people and Western industrialists shows strength for both. This article examines the improvement of Islamic financial matters in light of the contemplations of Muhammad Baqir Ash-Sadr, Karl Marx, and Max Weber in the humanistic perspective by taking a gander at the standards of worldwide Islamic financial matters in helping out a few non-Muslim nations. This research method uses library research, namely, taking information from books and scientific articles relevant to the problem to be answered. The consequences of this study show that the reasoning of Marx and Weber about the Islamic monetary framework encountering a decay was gone against by Muhammad Baiqr Sadr. That's what sadr censures if Marxism denies things connected with a powerful way of thinking; without anyone else, Marxism has isolated itself from things not related to science. The standards of Islamic lessons as the principal reason for making progress in business are demonstrated to have the option to contend worldwide. For instance, Saudi Aramco organizations, Islamic Development Bank (IDB), Qatar National Bank (QNB), Ooredoo, and the Fly Emirad Company are clear confirmations that they are huge organizations and impact financial backers in Western nations.